Synergistic effects of Monel 400 filler wire in gas metal arc welding of CoCrFeMnNi high entropy alloy - Shen, Jiajia; Taek Choi, Yeon; Gonçalves, Rita; Schell, Norbert; Yang, Jin; Zeng, Zhi; Catarina Baptista, Ana; Seop Kim, Hyoung; Oliveira, J.P. (Materials & design, 2024)
[Display omitted] •Welding the as-rolled CoCrFeMnNi high entropy alloy using Monel 400 filler wire via gas metal arc technique was conducted.•Welded joints were successfully obtained with full penetration and free of defects.•The weld thermal cycle changes both the microstructure features and texture distribution components across the welded joint.•The observed softening behavior within the heat affected zone is attributed to the release of pre-stored strain energy, coupled with solid-state transformations encompassing recovery, recrystallization, and grain growth.•Tensile testing, combined with DIC, reveals that fractures occur near the weld toe because of the softening effect, which activates stress concentrations.•The potential of utilizing CoCrFeMnNi joints as viable engineering structures is demonstrated. Weldability plays a crucial role in the journey of high entropy alloys towards their engineering applications. In this study, gas metal arc welding was performed to join an as-rolled CoCrFeMnNi high entropy alloy using Monel 400 as the filler wire. The present research findings demonstrate a favorable metallurgical chemical reaction between the Monel 400 filler and the CoCrFeMnNi high entropy alloy, resulting in compositional mixing within the fusion zone that promotes a solid-solution strengthening effect, counteracting the typical low hardness associated to the fusion zone of these alloys. The weld thermal cycle induced multiple microstructure changes across the joint, including variations in the grain size, existing phases and local texture. The grain size was seen to increase from the base material toward the fusion zone. An FCC matrix and finely sparse Cr-Mn-based oxides existed in both base material and heat affected zone, while in the fusion zone new FCC phases and carbides were formed upon the mixing of the Monel 400 filler. The role of the filler material on the fusion zone microstructure evolution was rationalized using thermodynamic calculations. Texture shifted from a γ-fiber (in the base material) to a strong cubic texture in the fusion zone. Digital image correlation during tensile testing to fracture coupled with microhardness mapping revealed that, stemming from the process-induced microstructure changes, the micro and macromechanical response differed significantly from the original base material. This study successfully established a correlation between the impact of the process on the developed microstructural features and the resultant mechanical behavior, effectively assessing the processing-microstructure-properties relationships towards an improved understanding of the physical metallurgy associated to these advanced engineering alloys. In conclusion, this work provides an important theoretical framework and practical guidance for optimizing the engineering applications of high entropy alloys.